Development of deterministic runoff prediction model for micro-watersheds of Dal Catchment of Kashmir Valley, India - BHAT, OWAIS AHMAD; KUMAR, ROHITASHW; KUMAR, MUKESH; ALTAF, YASIR (Journal of Soil and Water Conservation, 2022)
The present study was conducted in five micro watersheds of Dal catchment in Kashmir valley to evaluatethe runoffyield. Linear and log linear model were developed for annual runoff. At micro level planning, watershed delineation and stream network are the preliminary steps for watershed prioritization, integrated watershed management and sustainable development of natural resources within the watershed. Geomorphological parameters of watershed have been determined, which are interrelated to parameters of watershed characteristics. The value of drainage density was comparatively on higher side ranging from 4.91-5.95 km km2. The catchment shows low value of bifurcation ratio and the drainage pattern has not been distorted by structural disturbance. The study has shown that the watershed is in conformity with the Horton’s law of stream numbers and stream lengths. The runoff developed model has close agreement between observed and predicted values at 5% level of significance. The R2 value between mean observed and predicted runoff was 0.87 which shows close agreement between field observed and model predicated runoff value.The morphologic parameters have been proved to be efficient tools for morphometric analysis indicates the presence of dendritic drainage pattern pointing out favorable conditions in selecting the soil and water conservation measures and water harvesting systems.